The Relationship Between Ownership Structure and Company Performance - Komang Tri WAHYUNI; I Gusti Agung Krisna LESTARI (Indonesia Strategic Sustainability, 2021)
This study is conducted to analyze the impact of ownership structure on the firm's value. Dimensions of ownership structure are represented by concentrated ownership and managerial ownership. The samples of this study are LQ45 companies listed on the Indonesian Stock Exchange (IDX) for the period 2016-2020. Total Observation of 125 was determined by the purposive sampling method. Both performance measures: ROE and ROA, are used to measure the performance of the corporate. There is market capitalization as the control variable. This study uses Ordinary Least Square (OLS) for hypotheses testing. The results show that Ownership concentration has a negative effect with statistical insignificance on corporate performance (measured by ROE); however, it is positive and significant on corporate performance (measured by ROA). Managerial ownership found insignificance in corporate performance. However, it has a positive effect on corporate performance (measured by ROE) and a negative effect on corporate performance (measured by ROA). The research found that the size of the firm effect (measured by market capitalization) has a positive effect with statistical significance on corporate performance. The implication of this study showed that all companies should take concentrated ownership, which creates majority and minority shareholders creating a potential conflict that may affect the value of the firm and consider size effect on the performance of the corporate